Keggin type polyoxometalate H4[αSiW12O40].nH2O as intercalant for hydrotalcite - Neza Rahayu Palapa; Muhammad Said (Science and Technology Indonesia, 2016)
The synthesis of hydrotalcite and polyoxometalate H4[αSiW12O40].nH2O with the ratio (2:1), (1:1), (1:2) and (1:3) has been done. The product of intercalation was characterized using FT-IR spectrophotometer, XRD, and TG-DTA. Polyoxometalate H4[αSiW12O40].nH2O intercalated layered double hydroxide was optimised to use as adsorbent Congo red dye. Characterization using FT-IR was not showing the optimal insertion process. The result using XRD characterization was showed successful of polyoxometalate H4[αSiW12O40].nH2O inserted layered double hydroxide with a ratio (1:1) which the basal spacing was expanded from 7,8 Ȧ to 9,81 Ȧ. Furthermore, the thermal analysis was performed using TG-DTA. The result show that the decomposition of polyoxometalate H4[αSiW12O40].nH2O intercalated hydrotalcite with ratio (1:1) was occured at 80oC to 400oC with a loss of OH in the layer at 150oC to 220oC, and then the decomposition of the compound polyoxometalate H4[αSiW12O40].nH2O at 350oC to 420oC. Keywords: Hydrotalcite, Layered Double Hydroxide, Polyoxometalate, Intercalation